The threshold-voltage model of MOSFET devices with localized interface charge - Jean, YS; Wu, CY (My University, 1997)
A new analytic threshold-voltage model for a MOSFET device with localized interface charges is presented, Dividing the damaged MOSFET device into three zones, the surface potential is obtained by solving the two-dimensional (2-D) Poisson's equation, Calculating the minimum surface potential, the analytic threshold-voltage model is derived, It is verified that the model accurately predicts the threshold voltage for not only the fresh devices but also the damaged devices, Moreover, the Drain-Induced Barrier Lowering (DIBL) and substrate bias effects are also included in this model, It is shown that the screening effects due to built-in potential and drain bias dominate the impact of the localized interface charge on the threshold voltage, Calculation results show that the extension, position and density of localized interface charge are the main issues to influence the threshold voltage of a damaged MOSFET device, Simulation results using a 2-D device simulator are used to verify the validity of this model, and quite good agreements are obtained for various cases.